Need and Provision of Early Childhood Education (ECCE) in the National Educational Policies of Pakistan - Sara Siddique; Aurangzeb, Wajeeha (JECCE, 2024)
This article analyzed the need and provision of Early Childhood Care and Education (ECCE) in the national educational policies (1998, 2009, 2017) and other related documents to explore the factors that led to the introduction of ECCE in mainstream education in Pakistan. The document analysis of the national educational policies and other related reports indicate that for almost four decades, ECCE was narrowly addressed in the educational policies of Pakistan mainly because of the lack of prioritization. It also suggested that the significance of ECCE was acknowledged in the National Education Policy of 2009 for the first time and strengthened in the National Education Policy of 2017, due to several international commitments of Pakistan including the Dakar Framework of Action for Education for All 2000, The Millennium Developmental Goals (MDGs), the Sustainable Developmental Goals (SDGs) and its Vision 2030. The National Educational Policy of 2009, 2017 and the Development of Early Childhood Care and Education (ECCE) Curriculum are a few positive steps for the implementation of ECCE in Pakistan. Still, there is a need to monitor and evaluate the existing state and make a practical plan for positive reforms.